High consumption of ultra-processed foods among children and young people in the United States: challenges and solutions - Moura, Claudia de Saraiva; Carvalho, George Harrison Ferreira de (Revista JRG de Estudos Acadêmicos, 2025)
The consumption of ultra-processed foods (UPF) among children and adolescents in the United States has become a critical public health concern. These highly industrialized products represent more than 60% of the daily caloric intake in this age group, being associated with a number of chronic diseases such as obesity, type 2 diabetes and hypertension. The significant increase in the availability, convenience and advertising appeal of these foods has contributed to unhealthy eating habits, especially among low-income populations with lower schooling. This article is a narrative review of the literature and discusses the main challenges related to the high consumption of (UPF) by young Americans, highlighting social, economic, cultural and environmental factors. In addition, it explores the nutritional, psychological and metabolic impacts resulting from frequent intake of these products. Strategies and public policies to mitigate the problem are presented, including school programs, regulation of children’s advertising, community interventions and reforms in nutrition labelling. The shared responsibility between families, schools, food industry and governments is emphasized as fundamental for building healthier food environments. Finally, it is proposed a systemic and intersectoral approach to reduce the consumption of (UPF) and promote the integral health of children and adolescents.